Field-Based Characterization of Peste des Petits Ruminants in Sheep in Romania: Clinical, Pathological, and Diagnostic Perspectives - Romică Iacobescu-Marițescu; Adriana Morar; Viorel Herman; Emil Tîrziu; János Dégi; Kálmán Imre (Veterinary Sciences)
Peste des petits ruminants is a highly contagious transboundary viral disease that poses a serious threat to small ruminant populations worldwide. In 2024, seven outbreaks of PPR were recorded in sheep flocks from Timiș County, marking the second confirmed incursions of peste des petits ruminants virus (PPRV) in Romania. This study aimed to document the clinical presentation, pathological findings, and diagnostic confirmation with these field outbreaks. Comprehensive field investigations were carried out between July and September 2024, including clinical examinations, post mortem analysis, serological screening, and molecular detection using reverse transcription polymerase chain reaction (RT-PCR). A total of 13,203 sheep were evaluated, with an overall mortality rate of 12.77%. Characteristic clinical signs included mucopurulent nasal discharge, oral erosions, respiratory distress, and diarrhea. Gross lesions observed during necropsy included hemorrhagic bronchopneumonia, bile-stained liver, catarrhal enteritis, and mucosal hemorrhages. Serological testing revealed flock-level seroprevalence rates ranging from 46.7% to 80.0%, with higher rates observed in older animals. RT-PCR confirmed PPRV infection in all affected flocks. Our findings provide strong evidence of virulent PPRV circulation in an area where the virus had not been reported before. The results highlight an urgent need to strengthen surveillance systems, enhance diagnostic capacity, and foster cross-border collaboration. These field-based insights can contribute to both national and international efforts aimed at controlling and ultimately eradicating the disease.